Dietary protein/lipid ratio affects the growth performance and one-carbon metabolism mediated by folate in juvenile razor clam Sinonovacula constricta - Yuxiang Zhu; Kai Liao; Yang Liu; Hailong Huang; Yang Zhang; Hui Ge; Deshui Chen; Bin Ma; Jilin Xu (Aquaculture Reports)
The current research on artificial feed, nutritional requirements, and metabolism of bivalves is extremely limited. Here, we studied the effects of dietary protein/lipid ratios on the growth and folate metabolism of juvenile clam Sinonovacula constricta. Four microcapsule feeds were formulated with different protein (27–48 %) and lipid (2–14 %) levels, designated as follows: P48L2 (48 % protein and 2 % lipid), P41L6, P34L10, and P27L14 groups. Clams, initially measuring 2.7 ± 0.08 mm in shell length, were fed these diets for a period of 14 days. Results showed the optimal dietary protein/lipid ratio for juvenile clams was predicted to be 4.6. The lipid level of clam exhibited an upward trend as the dietary protein/lipid ratio decreased, and the appropriate protein/lipid ratio enhanced the activities of amylase, catalase, and superoxide dismutase. Transcriptome analysis showed that the pyrimidine/purine metabolism and one carbon pool by folate in the clam fed P41L6 diet was downregulated relative to those fed P34L10 and P27L14 diets. Meanwhile, compared with P34L10 group, the clam in the P41L6 group exhibited decreased levels of 5-methyltetrahydrofolate and folate, and increased levels of L-methionine and S-adenosylmethionine. Our results for the first time revealed that the optimal dietary protein/lipid ratio for clam was 4.6. Furthermore, the high-protein/low-lipid diet may inhibit growth by causing abnormal accumulation of metabolites in the methionine cycle and inhibiting the folate metabolism, ultimately resulting in reduced purine and pyrimidine synthesis. Our findings may provide indispensable theoretical support for formulating feeds of clam and understanding the relationship between dietary nutrient intake ratios and folate-mediated one-carbon metabolism.